Thinking together: How group argumentation boosts fake news recognition - Diana Carbone; Francesco Marcatto; Donatella Ferrante (PLoS ONE, 2026)
In a study with 111 college students, we present preliminary evidence that group discussion may improve the ability to recognize fake news. In the study, participants judged the veracity of news stories before and after participating in a group discussion or writing an individual reflection. The results showed that accuracy improved only in the case of fake news discussed in groups, while individual reflection was not sufficient to improve performance. An improvement in accuracy for individually evaluated fake news was observed only when these news items were presented after the group-discussed fake news in the experimental order, consistent with a transfer effect of group discussion on accuracy. Group argumentation produced positive effects on accuracy even in group interactions with inaccurate participants. The findings are in line with the Argumentative Theory of Reasoning.